2012
DOI: 10.1111/j.1365-3059.2012.02684.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of botrytis bunch rot in organic wine grapes with the yeast antagonist Candida sake CPA‐1

Abstract: The aim of this research was to confirm the efficacy of the yeast antagonist Candida sake CPA-1 in suppressing botrytis bunch rot development, in an organic vineyard under Mediterranean conditions for two seasons, and compare its performance with that of two biologically based products currently registered for botrytis bunch rot control in New Zealand. In 2009, treatments applied were: commercial formulations of Ulocladium oudemansii (BOTRY-Zen ® ) and chitosan (ARMOUR-Zen ® ), C. sake CPA-1 combined with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 22 publications
4
67
2
Order By: Relevance
“…Donmez et al (2011) showed that antagonistic bacterial strains Bacillus C6, Brevibacterium MFD-47, Enterobacter MFD-81 and Pantoea MFD-232 inhibited Botrytis cinerea and they have a potential use in sustainable strawberry production. Calvo-Garrido et al (2012) reported that Candida sake consistently provided effective control of botrytis bunch rot in grape under different meteorological and disease pressure conditions, thereby improving its potential for future commercial applications.…”
Section: Introductionmentioning
confidence: 98%
“…Donmez et al (2011) showed that antagonistic bacterial strains Bacillus C6, Brevibacterium MFD-47, Enterobacter MFD-81 and Pantoea MFD-232 inhibited Botrytis cinerea and they have a potential use in sustainable strawberry production. Calvo-Garrido et al (2012) reported that Candida sake consistently provided effective control of botrytis bunch rot in grape under different meteorological and disease pressure conditions, thereby improving its potential for future commercial applications.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, this product demonstrated some efficacy against BBR when used alone (Calvo‐Garrido et al . ). These findings stimulated the research on the mechanisms by which B. cinerea control was achieved by fatty acid–based products, such as FC and PRT.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, a less concentrated formulation of FC (Fungicover ® Base) achieved similar reductions of B. cinerea in field applications (Calvo‐Garrido et al . ) and laboratory experiments (Calvo‐Garrido et al . ) and, to our knowledge, the present research and the client reports on PRT published by Henry Manufacturing Ltd (http://www.henrymanufacturing.co.nz/products/protectorhml/) are the only studies showing efficacy of fatty acid–based NPs against B. cinerea of grapes in the field and in laboratory studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this concept, several new approaches to strengthen biological control are being studied. These approaches include the combination of two or more antagonistic strains, the induction of natural biological processes (e.g., inducing systemic resistance) (El Ghaouth et al, 2003;Reglinski et al, 2005), the use of natural antimicrobial products (e.g., chitosan, lysozyme) and plant resistance (Calvo-Garrido et al, 2013, 2014bDroby et al, 2009). In addition, the identification and use of yeasts, which are normal components on the surface of grape berries, have been studied for their capacity as biocontrol agents (Nally et al, 2012;Parafati et al, 2015;Vargas et al, 2012).…”
Section: Biological Controlmentioning
confidence: 99%